AN ANALYSIS OF MORAL VALUES FOUND IN ROBERT FROST'S SELECTED POEMS - ., I Wayan Rengkuh Febri Subrata; ., Kadek Sonia Piscayanti, S.Pd., M.Pd.; ., G.A.P. Suprianti, S.Pd., M.Pd. (Universitas Pendidikan Ganesha, 2017)
AN ANALYSIS OF MORAL VALUES FOUND IN ROBERT FROST SELECTED POEMS By I Wayan Rengkuh Febri Subrata, NIM 1112021079 English Education Department ABSTRACT This research is entitled â€œAn Analysis of Moral Values Found in Robert Frost Selected Poemsâ€. This research that has been written in for analyzing the moral values point from the six selected poems namely : A Patch Of Old Snow, Dust Of Snow, Nothing Gold Can Stay, Devotion, A Question, and The Sound Of The Trees. This research use the library research method with supporting data from the internet. The Moral Values from the human behavior in good and bad. The first is A Patch Of Old Snow has a moral value to keep the kindness and love for peace and harmony. The second poem is Dust Of Snow that has a moral value of the forbidden way of the human action for killed himself. Killed himself as a part of the hell entrance or a wrong way of human choice in the new era. The third poem is A Question, that has a moral value for preventing ourself for the selfishness. Selfishness create the poverty and lack of humility. The fourth poem is devotion that has a moral value of unstoppable willpower of the human being for get the success point in their entire life. The fifth poem is Nothing Gold Can Stay that has a moral value of the beauty cannot stay in the long time. The sixth poem, The Sound Of The Trees has a moral value of the human consistency in staying in homeland because of the responsibilities and jobs. keyword : Key Words: Moral Values, A Patch Of Old Snow, Dust Of Snow, A Question, Devotion, Nothing Gold Can Stay, The Sound Of The Trees.